The relationship between age and education on syphilis infection among commercial sex workers - Amelia Amelia; Rini Handayani; Ira Marti Ayu; Erna Veronika (Journal of Midwifery and Nursing, 2025)
Sexually Transmitted Infections (STIs) remain a global public health issue, with syphilis being one of the most prevalent. Syphilis, caused by Treponema pallidum, is transmitted through sexual contact and from mother to fetus. It can spread to genital tissues, causing painful sores that impact mobility, daily activities, and income among commercial sex workers (CSWs). This study examines factors associated with syphilis incidence among CSWs. A quantitative study with an observational case-control design was conducted. A total of 129 respondents were selected through purposive sampling with a 1:2 ratio between the case group (43 CSWs diagnosed with syphilis) and the control group (86 CSWs without syphilis). Secondary data were obtained from medical records, while primary data were collected using questionnaires via Google Forms. Data analysis was performed using the Chi-Square test. The findings showed significant associations between age (OR: 7.479; p = 0.034) and education level (OR: 3.304; p = 0.022) with syphilis incidence. These results highlight the importance of age and education in syphilis occurrence. Targeted health interventions, including better education and improved healthcare access for CSWs, are essential in reducing syphilis cases.